Modeling and Analysis of Lung Water Content Using RF Sensor - Prapti Ganguly; Shreyasi Das; Amlan Chakrabarti; Jawad Yaseen Siddiqui (IEEE Open Journal of Instrumentation and Measurement)
Abnormal fluid buildup in the lungs, termed pulmonary edema (PE), is a result of congestive heart failure. It is a life-threatening condition, and early detection and prompt treatment can help save lives. In this article, we demonstrate the feasibility of using a microwave sensor to monitor changes in lung water content and hence detect PE. The research paper utilizes a combination of the Debye and Maxwell models, along with the Cole–Cole equation, to evaluate alterations in the dielectric properties and conductivity of lung tissue. By incorporating elements such as air and water found within the tissue, this dielectric model has been employed to foresee how lung tissues behave when subjected to different levels of hydration and inflation. A printed antenna resonating at 2.4 GHz was designed to work as a sensor. The static dielectric parameters of lung tissue at various water volume fractions were calculated at 2.4 GHz using the Debye–Maxwell model. These parameters were substituted in the Cole–Cole equation to calculate the dielectric constant of lung tissue for different levels of water in the lungs. These values were then substituted in the simulation environment, where the sensor is placed on blocks modeling the human thorax. This work is a first of its kind where the dielectric parameters at different levels of hydration have been previously estimated using mathematical models and substituted accordingly in the modeling environment to test the possibility of detection of PE with high precision. It was observed that the magnitude of the reflection coefficient values changes with increasing water volume fraction, making the microwave method of detection of PE feasible and a reliable technique.